The Role of Creativity and Innovation in Menus in Attracting Millennial Consumers to the Culinary Business - Lie, Oleh Tjhing Man; Hadi, Bawa Mulyono; Mahmudi, Mahmudi (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
This study aims to examine the influence of menu creativity and innovation on the purchasing interest of millennial consumers in the culinary business. The background of this study is based on changes in the consumption behaviour of millennials, who not only pursue taste but also pay attention to visual aspects, unique value, and emotional experiences when choosing food. This study employs a quantitative-descriptive approach using a survey method targeting 120 millennial respondents who actively consume creative and innovative culinary offerings. The analysis technique used is multiple linear regression with the assistance of SPSS. The results of the study indicate that menu creativity (β = 0.341; p < 0.001) and menu innovation (β = 0.468; p < 0.001) have a positive and significant effect on millennial consumers' purchasing interest, both partially and simultaneously (R² = 0.576; F = 47.53; p < 0.001). These findings support the Stimulus-Organism-Response (SOR) theory, which explains that creativity and innovation as stimuli can shape consumers' perceptions and emotions, ultimately leading to purchasing decisions. This study provides strategic implications for culinary business actors to integrate creative design and innovative approaches in product development to be more relevant to the preferences of the digital-native generation.